Pengaruh Financial Distress, Ukuran Perusahaan dan Kepemilikan Institusional Terhadap Audit Delay - Sitompul, Marthin okuli sitompul (Asosiasi Dosen Akuntansi Indonesia, 2025)
This article aims to analyze the time it takes for audits in the advertising, printing, and media subsector to be completed in relation to financial distress, company size, and institutional policies. When documenting data collection, methodology is utilized. Tests for classical assumptions, regression, correlation, and determination are among the many analytical methods used, along with partial and simultaneous tests. Here are the findings from this investigation that audit delays were directly related to company size, financial distress, and other relevant factors. The ownership structure of institutions is changing. Results from the concurrent tests reveal that financial hardship, firm size, and institutional loyalty positively affect audit delay; however, these effects are not statistically significant. Partial test results indicate that there is a negative correlation between financial hardship and audit delay, but that this correlation is not statistically significant. Similarly, the correlation between firm size and audit delay is negative, but it is not statistically significant. On the flip side, audit delay is negatively correlated with institutional loyalty.